Eating disorder prevention initiatives for athletes: A review. Issue 3 (2nd April 2016) - Bar, Rachel J.; Cassin, Stephanie E.; Dionne, Michelle M.
Abstract: A substantial amount of evidence suggests that collegiate and elite athletes involved in weight-sensitive sports are at greater risk of developing eating disorders (EDs) than the general population. With the limited effectiveness of treatment for EDs, prevention of EDs has been broadly considered in the literature. The present paper reviewed the existing literature on ED prevention programmes for athletes in order to determine the current status of prevention programmes and recommend future directions. The available literature suggests that selective, primary interventions with multiple targets and an interactive multimodal approach appear most effective. Current challenges in the field, including lack of longitudinal research, hesitation by the sport community to be involved in ED research and poor cross-field communication and collaboration, are also explored. The lack of dissemination of evidence-based prevention programmes and the simultaneous promotion of prevention programmes that have not yet been empirically examined are also discussed. Based on these observations future directions are recommended.